Phenotypic Diversity of Doum Palm (Hyphaene compressa), a Semi‐Domesticated Palm in the Arid and Semi‐Arid Regions of Kenya - Agnes Omire; Nancy L. M. Budambula; Johnstone Neondo; Robert Gituru; Cecilia Mweu (Scientifica)
Hyphaene compressa is an economically important palm in Africa. Despite its significant role in the livelihoods of rural communities, the diversity of doum palm is poorly documented and studied. In addition, it has no model descriptor that can aid such studies. Ninety H. compressa accessions collected from Northern, Eastern, and Coastal regions of Kenya were examined to determine the morphological variability of the vegetative and fruit traits of H. compressa and to identify its morphotypes for improvement. A total of 19 morphological characters including seven quantitative and 12 qualitative traits of fruit and vegetative traits were selected. Linear mixed-effects models, principal component analysis, and linear discriminant analyses were used to assess the variation in the morphological traits of doum palm based on the regions. Hierarchical clustering was performed to identify the morphotypes of H. compressa. There was variability in H. compressa morphological traits, particularly at the Kenyan Coast. All seven quantitative traits were able to effectively discriminate doum palm phenotypically p≤0.001. The 90 accessions clustered into five morphotypes designated as 1, 2, 3, 4, and 5. Morphotype 4 was specific only to the Coastal region. Morphotype 5 had the tallest trees with the biggest fruits and included palms from Eastern and Coastal regions making it the best morphotype for fruit traits. This study will inform the domestication, improvement, and conservation of H. compressa by selecting elite accessions.